2019
DOI: 10.1111/bjh.16097
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and bruising in Osteogenesis Imperfecta: International Society on Thrombosis and Haemostasis bleeding assessment tool and haemostasis laboratory assessment in 22 individuals

Abstract: Osteogenesis imperfecta (OI) is characterized by susceptibility to bone fractures. Other symptoms, such as easy bruising and bleeding complications during surgery necessitating transfusions, have also been reported. The aim of the cross-sectional pilot study was to assess the bleeding and bruising tendency in OI patients and to screen for possible underlying haematological disorders. Bleeding tendency was investigated using the International Society on Thrombosis and Haemostasis bleeding assessment tool (ISTH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
(44 reference statements)
0
8
1
Order By: Relevance
“…Coagulation, fibrinolysis and platelet function tests were normal in all patients investigated. Hyperfibrinolysis, previously identified as a possible cause for mild bleeding disorders in adults with OI, 5 was not confirmed in our study. VWF, soluble E‐selectin and sTM were also explored as markers of endothelial activation in vascular disorders 6 .…”
Section: Id Sex Age (Years) Blood Group Oi Type Isth‐bat Bs Family Incontrasting
confidence: 98%
“…Coagulation, fibrinolysis and platelet function tests were normal in all patients investigated. Hyperfibrinolysis, previously identified as a possible cause for mild bleeding disorders in adults with OI, 5 was not confirmed in our study. VWF, soluble E‐selectin and sTM were also explored as markers of endothelial activation in vascular disorders 6 .…”
Section: Id Sex Age (Years) Blood Group Oi Type Isth‐bat Bs Family Incontrasting
confidence: 98%
“…The loss and degenerative changes of smooth muscle cells in blood vessels is a major histopathological feature of an intracranial aneurysm, and it is well known that intracranial aneurysms can easily rupture and produce subarachnoid hemorrhages [ 8 ]. Supporting our hypothesis, osteogenesis imperfecta caused by mutations in type I collagen genes ( COL1A1/COL1A2 ) is associated with hemorrhagic diathesis, and is also hypothesized to be associated with vascular fragility [ 32 , 33 ]. In addition, previous studies reported abnormalities in the cerebral arterial system in osteogenesis imperfecta [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 84%
“…Qualitative platelet abnormalities, such as impaired clot retraction, reduced ristocetin cofactor, abnormal platelet morphology (large platelets), and impaired aggregation capacity, have been reported. Several studies have reported that patients with OI show increased capillary fragility, reduced factor VIII-related antigens, prolonged thromboplastin time, and extended bleeding time on hemostatic testing ( 10 , 11 ). Patients with OI may also have an underlying early diastolic cardiac dysfunction that requires special attention ( 12 ).…”
Section: Discussionmentioning
confidence: 99%